The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1248/bpb.b14-00273
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Suppresses β-Casein Expression <i>via</i> Inhibition of the Signal Transducer and Activator of Transcription 5 (STAT5) Protein Phosphorylation in Human Mammary Epithelial Cells MCF-12A

Abstract: Serotonin (5-hydroxytryptamine; 5-HT) has an important physiological role in controlling lactation, namely, milk volume homeostasis, within mammary glands. The objectives of this study were to evaluate whether exogenous 5-HT can suppress β-casein expression, a differentiation marker, produced in human mammary epithelial cells, and to determine whether 5-HT can attenuate β-casein signaling via the prolactin (PRL) receptor (PRLr) and Janus kinase 2/signal transducer and activator of transcription 5 (STAT5) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Treatment with 100 µM 5-HT for 72 h inhibited β-casein expression, and this inhibition was associated with the suppression of STAT5 phosphorylation. 15) In this study, we found that 30 µM 5-HT inhibited β-casein mRNA expression in a time-dependent manner (Fig. 1A).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Treatment with 100 µM 5-HT for 72 h inhibited β-casein expression, and this inhibition was associated with the suppression of STAT5 phosphorylation. 15) In this study, we found that 30 µM 5-HT inhibited β-casein mRNA expression in a time-dependent manner (Fig. 1A).…”
Section: Discussionmentioning
confidence: 50%
“…[12][13][14] In our previous study, PRL treatment induced β-casein expression in the human mammary epithelial cell line MCF-12A via activation of the Jak2/STAT5 pathway. We also showed that 5-HT treatment decreased β-casein levels, with a concomitant reduction in STAT5 phosphorylation (pSTAT5), 15) suggesting that suppression of β-casein by 5-HT was associated with reduced STAT5 phosphorylation. These results implied that endogenous 5-HT in MCF-12A cells may be secreted and signal in an autocrine and/or paracrine manner in MCF-12A cells.…”
Section: -5)mentioning
confidence: 60%
See 2 more Smart Citations
“…102 Additionally, it is already known that PY-STAT5 signaling in the hypothalamus is involved in regulating appetite and sex-biased changes in body weight. 103 It has been shown already that 5-HT suppresses STAT5 expression and PY-STAT5 activation, 104 and 5-HT-receptor and dopaminergic D1, D2 receptor antagonists also inhibit PY-STAT5 activation (e.g., pimozide). 105,106 We suggest that consideration of mechanisms in such models also include the central effects of 5-HT at the level of the hypothalamus and the arcuate nucleus, and sex-specific changes in the patterns of GH secretion and STAT5 activation.…”
Section: Neuroendocrine Stat5-anchored Mechanisms Of Sex Bias In Vascmentioning
confidence: 99%